The study on factors that influence housing price in Malaysia - Othman, Hamizah (2017)
The main purpose of this study is to measure the relationship between macroeconomic variables and the housing price. This paper examines empirically whether the increasing trend in the Malaysian housing price is related to changes in the interest rate, inflation rate and consumer price index. The paper is exploratory in nature. The empirical data were collected from DataStream from January 2007 until December 2016. The paper provides empirical results that the interest rate, inflation rate and consumer price index are the key determinants of housing price. The paper is useful for speculators, investors and buyers to know which factors to account for in housing investment decision. This paper can serve as a guide for the government in stabilizing the residential housing price in Malaysia.